Human rights : an interdisciplinary approach - Freeman, Michael , 1936- (Key concepts series, 2011)
Introducing readers to the theory and practice of human rights, this text emphasises how the experiences of the victims of human rights violations are related to legal, philosophical and social-scientific approaches to human rights